Assessment of Nurses' Perception toward Application of Evidence Based Practice Approach - Nour Al-huda Muhannad Mousa; Jihad Jawad Kadhim (Kufa Journal for Nursing Sciences)
Background Evidence-based nursing practice (EBNP) has become one of the most effective methods for improving patient outcomes and the quality of care as well as delivering cost-efficient health care. Nurses' perspectives are critical to the successful adoption of evidence -based practice. While positive views regarding EBP serve as a foundation for developing appropriate nursing approaches to improve patient care, there is a noticeable gap between belief in evidence-based practice advantages and actual implementation.